1982
DOI: 10.1017/s0043174500026114
|View full text |Cite
|
Sign up to set email alerts
|

The Antagonistic Action of 2,4-D and Bromoxynil on Glyphosate Phytotoxicity to Barley (Hordeum vulgare)

Abstract: The absorption, translocation, metabolism, and retention of an isopropylamine formulation of glyphosate [N-(phosphonomethyl)glycine] in the presence and absence of the commercial dimethylamine salt and isooctyl ester formulations of 2,4-D [(2,4-dichlorophenoxy)acetic acid], or the commercial isooctyl ester formulation of bromoxynil (3,5-dibromo-4-hydroxybenzonitrile) was investigated in barley (Hordeum vulgare L. 'Summit′). In all treatments, absorption of 14C-glyphosate continued for up to 24 h, but no furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…2,7) For example, the antagonism of mixtures of auxin herbicides with acetyl-CoA carboxylase (ACCase)-inhibiting herbicides (e.g., diclofopmethyl, haloxyfop-methyl, or fenoxaprop-methyl), glyphosate, or paraquat has led to weed-control failure. [8][9][10][11][12][13][14][15][16] Such antagonism can be due to increased metabolism or reduced uptake and translocation induced by 2,4-D. 14,17) Photosystem II (PSII)-inhibiting herbicides (PSII herbicides) inhibit the photosynthetic electron flow through photosystem II. PSII herbicides include S-triazines, triazinones, uracils, ureas, phenylcarbamates, anilides, cyanophenols, and dinitrophenols.…”
Section: Introductionmentioning
confidence: 99%
“…2,7) For example, the antagonism of mixtures of auxin herbicides with acetyl-CoA carboxylase (ACCase)-inhibiting herbicides (e.g., diclofopmethyl, haloxyfop-methyl, or fenoxaprop-methyl), glyphosate, or paraquat has led to weed-control failure. [8][9][10][11][12][13][14][15][16] Such antagonism can be due to increased metabolism or reduced uptake and translocation induced by 2,4-D. 14,17) Photosystem II (PSII)-inhibiting herbicides (PSII herbicides) inhibit the photosynthetic electron flow through photosystem II. PSII herbicides include S-triazines, triazinones, uracils, ureas, phenylcarbamates, anilides, cyanophenols, and dinitrophenols.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous research indicated that 2,4-D in both butoxyethyl ester and diethanolamine formulations conferred antagonism against glyphosate isopropylamine salt in wheat but no such antagonism with the isopropylamine formulation of 2,4-D. 29) Moreover, isooctyl ester and dimethylamine formulations of 2,4-D antagonized the efficiency of glyphosate isopropylamine salt in barley. 30) In our current study, interactions between the 2-ethyl hexyl ester or dimethylamine plus monomethylamine formulation of 2,4-D and glyphosate potassium salt were examined in barnyard grass, and it was found that both the ester and amine forms of 2,4-D were antagonistic to glyphosate potassium salt (Table 1; Fig. 1).…”
Section: Discussionmentioning
confidence: 73%
“…The mechanisms of reduced glyphosate uptake and translocation by 2,4-D are not clear but may be due to the chemical complex through the cation exchange 29) and the physical or physiological interactions. 8,16,29,30) The chemical forms of 2,4-D and glyphosate were reported to have an impact on the interactions. For instance, previous research indicated that 2,4-D in both butoxyethyl ester and diethanolamine formulations conferred antagonism against glyphosate isopropylamine salt in wheat but no such antagonism with the isopropylamine formulation of 2,4-D. 29) Moreover, isooctyl ester and dimethylamine formulations of 2,4-D antagonized the efficiency of glyphosate isopropylamine salt in barley.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the epidermal structure plays an important role. Because the olive leaf cuticle grows thicker as the leaf expands (León and Bukovac, 1978), olive plants may absorb less chemical than other glyphosatesusceptible plant species such as barley (Hordeum vulgare L.), which can absorb as much as 27% of the total applied herbicide (O'Donovan and O'Sullivan, 1982). Similarly, leaves from longer, older suckers have thicker cuticles than those from shorter, younger suckers, decreasing the absorption of 14 C-glyphosate.…”
Section: Resultsmentioning
confidence: 99%
“…Glyphosate is a nonselective, highly translocated herbicide that is absorbed by leaves and stems and accumulates in the actively growing parts of the plants (Caseley and Coupland, 1985). Translocation, however, can be considerably reduced when combined with 2,4-D-like herbicides such as MCPA (O'Donovan and O'Sullivan, 1982). No information exists on the absorption and movement of glyphosate in olive trees.…”
mentioning
confidence: 99%